2020
DOI: 10.1109/jeds.2020.2986940
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Charge-Sharing-Free Dynamic Logic Gates Employing Transistors With Multiple Independent Inputs

Abstract: Charge sharing poses a fundamental problem in the design of dynamic logic gates, which is nearly as old as digital circuit design itself. Although, many solutions are known, up to now most of them add additional complexity to a given circuit and require careful optimization of device sizes. Here we propose a simple CMOS-technology compatible transistor level solution to the charge sharing problem, employing a new class of field effect transistors with multiple independent gates (MIGFETs). Based on mixed-mode s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[26] Additionally, it has been predicted by simulations that exploiting three-gate RFETs, compact realizations of XOR and majority (MAJ) based combinatorial circuits can be envisioned using a lower number of transistors than in classical CMOS technology. [8] Based on these investigations a number of circuit level features, such as dynamic reconfiguration, [26,27] intrinsic XOR, [28] and wired-AND capabilities [29] as well as control of threshold voltage, [30] and suppression of parasitic charge sharing effects in dynamic logic gates, [31,32] have been demonstrated for RFETs, providing additional benefits over their CMOS counterparts. In this respect, fabricating reliable and reproducible metal-semiconductor junctions is essential, as the injection of charge carriers highly depends on the metal-semiconductor interface, junction area, and its incorporated energy barrier.…”
mentioning
confidence: 99%
“…[26] Additionally, it has been predicted by simulations that exploiting three-gate RFETs, compact realizations of XOR and majority (MAJ) based combinatorial circuits can be envisioned using a lower number of transistors than in classical CMOS technology. [8] Based on these investigations a number of circuit level features, such as dynamic reconfiguration, [26,27] intrinsic XOR, [28] and wired-AND capabilities [29] as well as control of threshold voltage, [30] and suppression of parasitic charge sharing effects in dynamic logic gates, [31,32] have been demonstrated for RFETs, providing additional benefits over their CMOS counterparts. In this respect, fabricating reliable and reproducible metal-semiconductor junctions is essential, as the injection of charge carriers highly depends on the metal-semiconductor interface, junction area, and its incorporated energy barrier.…”
mentioning
confidence: 99%
“…[13] Importantly, the possibility of changing the configuration of each transistor within a circuit enables a reconfiguration of its specific logic functions during operation. [32] Further, the bidirectional nature of reconfigurable transistors is a clear advantage for flexible and adaptive circuit design, as equivalent results can be obtained by swapping the signals between source/drain and V PG /V CG . [9] Considering that, simulations of multi-gate Ge-based RFET devices suggest a possible RFET operation down to a channel length of approximately L Ge = 50 nm, [16] our prototyping platform may paves the way for the development of key components of high-performance and low-power reconfigurable circuits, providing a prototyping platform for future energy-efficient systems as well as hardware security integrated circuits.…”
Section: Resultsmentioning
confidence: 99%
“…Reconfigurable devices are promising for applications in hardware security, where they can be applied to camouflage the circuit functionality [15], [16]. Furthermore, recent studies have shown that reconfigurable transistors, in particular devices with multiple independent gates, improve signal integrity in dynamic logic gates [17], [18]. They also have potential to foster non-traditional digital design styles, such as asynchronous and reversible logic [19].…”
Section: Related Workmentioning
confidence: 99%